Synthese und Luftvernetzung von Dimethylfulven-Copolymerisaten - Ulrich Schädeli; Markus Neuenschwander (CHIMIA)
Cationic copolymerization of 6,6-dimethylfulvene (1) with styrene, ethoxyethene, and cyclopentadiene has been investigated. For the system 1 (M1)/cyclopenta-diene (M2) copolymerization-parameters r1 = 21.5 and r2 = 0.053 have been determined; this shows that 1 is very easily incorporated into the growing polymer chain. Since copolymers of 1 contain structural units of type 2, they are sensitive to air, thus forming a polymeric network.